Single Cell Analysis: Label‐Free Optofluidic Nanobiosensor Enables Real‐Time Analysis of Single‐Cell Cytokine Secretion (Small 26/2018). Issue 26 (27th June 2018) - Li, Xiaokang; Soler, Maria; Szydzik, Crispin; Khoshmanesh, Khashayar; Schmidt, Julien; Coukos, George; Mitchell, Arnan; Altug, Hatice
Abstract : Dynamic monitoring and analysis of protein secretion from single cells remain challenges. In article number1800698, Hatice Altug and co‐workers present an optofluidic nanoplasmonic biosensor for real‐time monitoring of cytokine secretion. The label‐free system enables the detection and quantification of protein secretions from single cells while maintaining controlled conditions for cell activity. With integration into multifunctional microfluidic systems, this biosensor can be a powerful tool to characterize single‐cell signaling for basic and clinical research.